2011
DOI: 10.1021/ie102471b
|View full text |Cite
|
Sign up to set email alerts
|

An Overview of the Liquid−Liquid Equilibria of (Ionic Liquid + Hydrocarbon) Binary Systems and Their Modeling by the Conductor-like Screening Model for Real Solvents

Abstract: Ionic liquids (ILs), with their unique and tunable properties, are attracting the interest of both academia and refining companies as potential solvents for the extraction of specific compounds from hydrocarbons’ streams. For such a purpose, the knowledge of the mutual solubilities between ionic liquids and hydrocarbons is required. Experimental measurements for all these systems are impracticable due to the large number of possible combinations of ionic liquids and hydrocarbons. Thus, a deeper understanding o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
82
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 145 publications
(89 citation statements)
references
References 71 publications
7
82
0
Order By: Relevance
“…This is in agreement with the hydrogen bond acidities of ionic liquids (α) listed in Table 5, in which their cations play the principle role [18,90]. Further on, both studied ionic liquids are also proton acceptors through their anions (the respective hydrogen bond basicities β given in Table 5 are mainly anion controlled [18,90] [82,91,92].…”
Section: Discussionsupporting
confidence: 86%
“…This is in agreement with the hydrogen bond acidities of ionic liquids (α) listed in Table 5, in which their cations play the principle role [18,90]. Further on, both studied ionic liquids are also proton acceptors through their anions (the respective hydrogen bond basicities β given in Table 5 are mainly anion controlled [18,90] [82,91,92].…”
Section: Discussionsupporting
confidence: 86%
“…Strong interactions occurred between the π-electrons delocalized in the aromatic structure with the polar ionic liquids, especially with the pyridinium cation, which resulted in better solubility. Consequently, in this case, the main role of solubility, apart from van der Waals interactions and packing effects, was to induce dipole interactions (Marciniak et al, 2010;Marciniak et al, 2011;Ferreira et al, 2011;Domanska et al, 2012 N] + toluene) used in this study provided evidence that suggested the emergence of the lower critical solution temperature (LCST) phenomenon, where the phase separation of the solution occurs at high temperatures. Moreover, the experimental data (Lachwa et al, 2006); Domańska et al, 2009;Domanska et al, 2010;Marciniak et al, 2010) …”
Section: Resultsmentioning
confidence: 88%
“…Whereas the excess properties can be used to understand the interaction between ionic liquid and water in the mixture state. The COSMO-RS model has been successfully used in the past to estimate the thermodynamic properties of systems containing ionic liquids, including liquid-liquid equilibrium and activity coefficients of its mixture with water or organic solutes [52][53][54][55][56][57][58][59]. After evaluating the capacity of the COSMO-RS model to describe the experimental activity coefficients, this is used to analyze and discuss the molecular interactions that affect the mixing properties of the cholinium-ionic liquids and water, which are also supported by ab initio calculations [60][61][62][63] [15,64].…”
Section: Introductionmentioning
confidence: 99%